Discovery Learning Berbantuan Virtual Chemistry Laboratory untuk Meningkatkan Hasil Belajar Siswa - Paulina Hendrajanti (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
This study aims to improve student learning outcomes on Acid-Base Titration material in class XI MIPA 1 SMAN 4 Yogyakarta by applying the Discovery Learning model assisted by the Virtual Chemistry Laboratory for the 2020/2021 school year. The research method used is classroom action research by adopting Kurt Lewin's model in which each cycle contains planning, implementation, observation, and reflection activities. The implementation is in two cycles and each cycle consists of two online learning sessions. The subjects of this activity are students of class XI MIPA 1, with initial data on learning outcomes of classical knowledge and mastery during the pandemic under the KKM. Tools/instruments for data collection are observation sheets, test and non-test assessment instruments, Likert scale, and documentation. The results showed: (1) In the first cycle, the learning outcomes of the knowledge aspect = 85.70%; skill aspect = 88.16%; attitude aspect = 81,63 %; classical learning completeness = 94.44%, (2) In the second cycle the learning outcomes of the knowledge aspect = 86.44%; skill aspect = 92.72%; attitude aspect = 83.19%; classical learning completeness = 94.44%. The conclusion of the research is that the application of Discovery Learning assisted by Virtual Chemistry Laboratory involves mental activity and skills so that it can improve student learning outcomes on Acid-Base Titration material in class XI MIPA 1 SMAN 4 Yogyakarta in the 2020/2021 academic year.